PWE-004 Does robotic surgery lead to more patients requiring parenteral nutrition? analysis in a tertiary centre. (June 2019) - Bancil, Aaron; Boyer-Masfari, Saba; Nasr, Ikram
Abstract : Introduction: Robotic surgery techniques have revolutionised Urological surgery. It has thus been used more frequently in centres that are able to offer the technique. It is suggested that robotics increases the accuracy of dissection and helps enhances the preservation of neurovascular bundles.(1) Anecdotally it was noted that patients who had robotic surgery developed more nutritional complications than those patients who underwent non-robotic surgeries previously. On review of the literature, rates of paralytic ileus in non-robotic surgeries range from 7.–8% respectively. (2 3) Method: We analysed all patients who underwent robotic Urological surgery at Guy's & St Thomas' NHS Trust in the last 2 years (robotic cystectomies and prostatectomies). All patient post-operative notes were analysed and screened for the development of post-operative ileus and/or the requirement of Parenteral Nutrition (PN). Results: In total, 136 patients were analysed. Of these, 19 patients developed post-operative ileus (16 male, 3 female, average age 69.5), 13 developed post-operative ileus requiring PN (9 male, 4 female, average age 68.2) and 2 patients developed bowel obstruction which did not require nutritional support (both patients were male, aged 64 & 65 respectively). Therefore, 23.5% of patients developed post-operative ileus, which is higher than reported non-robotic post-operative ileus rates. Conclusion: Our results suggest that robotic surgery may lead to more patients requiring nutritional support post-operatively than those who had non-robotic surgery, according to previously reported rates. The increased proportion of ileus could be related to operating time. It is possible that with increased usage of the robotic technique, the operating time will decrease and thus levels of ileus will reduce. This also emphasises the importance of the involvement of a dedicated Nutrition team in these patients, which should include a Medical Consultant and highly-specialised pharmacists, nurses and dieticians. Further studies in larger cohorts are required. References: Challacombe BJ, Rose K, Dasgupta P. Laparoscopic radical and partial cystectomy. Actas Urol Esp [Internet] . 2005;1(4):188–95. Roghmann F, Trinh QD, Braun K, von Bodman C, Brock M, Noldus J, et al. Standardized assessment of complications in a contemporary series of European patients undergoing radical cystectomy. Int J Urol . 2014;21(2):143–9. Chang SS, Cookson MS, Baumgartner RG, Wells N, Smith JA. Analysis of early complications after radical cystectomy: Results of a collaborative care pathway. J Urol . 2002;167(5):2012–6.